Unsolicited Proposals : Competitive Solutions for Private Infrastructure - World Bank (Washington, DC, 2012)
This Note looks at systems some governments have used to transform unsolicited proposals for private infrastructure projects into competitively tendered projects. It focuses on the policies that Chile, the Republic of Korea, the Philippines, and South Africa have adopted for managing such proposals. A companion Note explores the problems associated with unsolicited proposals, especially the risks they raise for competition and transparency. Among private infrastructure projects reaching financial closure, the share that originated as unsolicited proposals varies across countries. In the Philippines about 15 percent of such projects have been unsolicited, while in the Republic of Korea the share is as high as 50 percent. The share is also significant in many other countries, and policymakers have begun to recognize the need for formal systems to manage these unsolicited proposals. Governments could use several approaches to handle unsolicited proposals. One option is simply to adopt a law prohibiting unsolicited projects-and some governments have done this. A second option is for governments to purchase the project concept and then award the project through a competitive bidding process in which no bidder has a predefined advantage. A third option-the one adopted in such countries as Chile, the Republic of Korea, the Philippines, and South Africa-is to offer the original proponent a predefined advantage in a competitive bidding process. Under this third option two main approaches have developed: the bonus system and the Swiss challenge system.